Development of sulfasalazine resistance in human T cells induces expression of the multidrug resistance transporter ABCG2 (BCRP) and augmented production of TNFα. Issue 2 (13th January 2004) - van der Heijden, J; de Jong, M C; Dijkmans, B A C; Lems, W F; Oerlemans, R; Kathmann, I; Schalkwijk, C G; Scheffer, G L; Scheper, R J; Jansen, G
Abstract : Objective: To determine whether overexpression of cell membrane associated drug efflux pumps belonging to the family of ATP binding cassette (ABC) proteins contributes to a diminished efficacy of sulfasalazine (SSZ) after prolonged cellular exposure to this disease modifying antirheumatic drug (DMARD). Methods: A model system of human T cells (CEM) was used to expose cells in vitro to increasing concentrations of SSZ for a period of six months. Cells were then characterised for the expression of drug efflux pumps: P-glycoprotein (Pgp, ABCB1), multidrug resistance protein 1 (MRP1, ABCC1), and breast cancer resistance protein (BCRP, ABCG2). Results: Prolonged exposure of CEM cells to SSZ provoked resistance to SSZ as manifested by a 6.4-fold diminished antiproliferative effect of SSZ compared with parental CEM cells. CEM cells resistant to SSZ (CEM/SSZ) showed a marked induction of ABCG2/BCRP, Pgp expression was not detectable, while MRP1 expression was even down regulated. A functional role of ABCG2 in SSZ resistance was demonstrated by 60% reversal of SSZ resistance by the ABCG2 blocker Ko143. Release of the proinflammatory cytokine tumour necrosis factor α (TNFα) was threefold higher in CEM/SSZ cells than in CEM cells. Moreover, twofold higher concentrations of SSZ were required to inhibit TNFα release from CEM/SSZ cells compared with CEM cells. Conclusion: Collectively, ABCG2 induction, augmented TNFα release, and less efficient inhibition of TNFα production by SSZ may contribute to diminished efficacy after prolonged exposure to SSZ. These results warrant further clinical studies to verify whether drug efflux pumps, originally identified for their roles in cytostatic drug resistance, can also be induced by SSZ or other DMARDs.